2006
DOI: 10.1021/ja060745q
|View full text |Cite
|
Sign up to set email alerts
|

XeCu Covalent Bonding in XeCuF and XeCuCl, Characterized by Fourier Transform Microwave Spectroscopy Supported by Quantum Chemical Calculations

Abstract: XeCu covalent bonding has been found in the complexes XeCuF and XeCuCl. The molecules were characterized by Fourier transform microwave spectroscopy, supported by MP2 ab initio calculations. The complexes were prepared by laser ablation of Cu in the presence of Xe and SF(6) or Cl(2) and stabilized in supersonic jets of Ar. The rotational constants and centrifugal distortion constants show the XeCu bonds to be short and rigid. The (131)Xe, Cu, and Cl nuclear quadrupole coupling constants indicate major redistri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

7
83
0

Year Published

2009
2009
2018
2018

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 138 publications
(90 citation statements)
references
References 56 publications
7
83
0
Order By: Relevance
“…[1][2][3] Since the synthesis of "Xe + PtF 6 À " by Bartlett and co-workers, [4,5] numerous compounds that contain xenon, [1] and certain analogues of krypton, [6] have been isolated and structurally characterized. In addition, mostly in the last decade, studies performed in cold matrices [7][8][9] and in the gas phase [10][11][12][13] have considerably expanded the scope of noble gas chemistry, and revealed novel compounds and bonding motifs. Theoretical calculations are also extensively employed to aid the interpretation of the experiments, and to explore the conceivable existence of still uncovered molecules and ions.…”
Section: Introductionmentioning
confidence: 99%
“…[1][2][3] Since the synthesis of "Xe + PtF 6 À " by Bartlett and co-workers, [4,5] numerous compounds that contain xenon, [1] and certain analogues of krypton, [6] have been isolated and structurally characterized. In addition, mostly in the last decade, studies performed in cold matrices [7][8][9] and in the gas phase [10][11][12][13] have considerably expanded the scope of noble gas chemistry, and revealed novel compounds and bonding motifs. Theoretical calculations are also extensively employed to aid the interpretation of the experiments, and to explore the conceivable existence of still uncovered molecules and ions.…”
Section: Introductionmentioning
confidence: 99%
“…However, Gerry [6][7][8][9][10][11] and co-workers have developed an elegant method by which the gas-phase metal halide M-X is produced in situ by laser ablation of the metal M in the presence of a gas-phase source of halogen atoms X and the Lewis base B. Some of the M-X molecules so produced then pick up a molecule of B to give BÁ Á ÁM-X.…”
Section: Introductionmentioning
confidence: 99%
“…This also allowed for an estimate of the stretching vibrational frequency for this bond. The error introduced by fixing the M-X distance is expected to be small, as previous theoretical [5,6,20,25] and experimental [2][3][4] work on these and similar systems has shown that these bond lengths are not greatly affected by the noble gas bonding to the metal. These calculations were performed at the MP2 level, with some test cal- energies were calculated at the MP2 geometries to obtain a better estimate of the interaction energies.…”
Section: Methodsmentioning
confidence: 94%
“…Experimentally, all of the coinage metal fluorides bonded to xenon have been observed, as well as xenon copper and silver chloride [2][3][4]. Numerous computational studies have been performed on these xenon complexes and closely related compounds such as the xenon coinage metal hydroxides [5,6] and the insertion compounds MNgX [7,8].…”
Section: Introductionmentioning
confidence: 99%